Enzymological description of multitemplate PCR-Shrinking amplification bias by optimizing the polymerase-template ratio - Ingr, Marek; Dostál, Jiří; Majerová, Taťána (Journal of theoretical biology, 2015)
Multitemplate polymerase chain reaction (PCR) is used for preparative and analytical applications in diagnostics and research. Classical PCR and qPCR are two basic setups with many possible experimental modifications. Classical PCR is a method of choice to obtain enough material for subsequent sophisticated applications such as construction of libraries for next-generation sequencing or high-throughput screening. Sequencing and Single Nucleotide Primer Extension (SNuPE) employ one-strand synthesis and represent a distinct variant of analytical DNA synthesis. In all these applications, maintaining the initial ratio of templates and avoiding underestimation of minority templates is desired. Here, we demonstrate that different templates can amplify independently at low template concentrations (typical in qPCR setups, in which the polymerase concentration is usually several orders of magnitude higher than the template concentration). However, rare templates can be diluted in an effort to keep DNA amplification in the exponential phase, or template concentration can be biased by differences in amplification efficiency. Moreover, amplification of templates present in low concentrations is more vulnerable to stochastic events that lead to proportional changes in the product ratio, as well as by incomplete amplification leading to chimera formation. These undesired effects can be compensated for by using highly processive polymerases with high and equal affinity to different primer-template complexes. Novel enhanced polymerases are desired. With increasing concentration of a primer-template of interest, the system becomes more deterministic. Nevertheless, marked deviation from independent exponential amplification occurs when the total template concentration starts to approach the polymerase concentration. The primer-template complexes compete for enzyme molecules, and the amount of products grows arithmetically-the system starts to obey Michaelis-Menten kinetics. Synthesis of rare products in a multitemplate mixture can run more easily under the detection limit in such conditions, although it would be unequivocally detectable in a single template assay. When fishing out rare template variants, the best processive polymerases should be used to decrease both amplification and detection limits. The possibility of stochastic events, should be taken into account to correctly interpret the obtained data.
Keywords: Computer Simulation; stochastické procesy; Stochastic Processes; genetické matrice; DNA Primers; Enzymes; Polymerase Chain Reaction; polymerázová řetězová reakce; enzymy; DNA primery; počítačová simulace; Templates, Genetic